Preliminary investigations on stone cutting sludge processing for a future recovery. (20th March 2018) - Zichella, Lorena; Bellopede, Rossana; Spriano, Silvia; Marini, Paola
Abstract: Solid waste management is a key component for the natural stone industry. In recent years, multiwire machines have been overtaking stone gang saw cutting technology. The advantages of these new cutting-edge technologies are high efficiency and performance, flexibility of use, high quality of the cut surfaces, very low environmental impact (low energy consumption, lowest concentration of heavy metals in the sludge, less waste) and lowest noise levels. There are many studies on the separation and recovery of sludge from cutting with the gang saw, but very few on diamond cutting sludges. In accordance with the European Commission's Thematic Strategy on the Prevention and Recycling of Waste (EC raw material strategies), it is important to perform a correct characterization of sludge from cutting with the new technologies, in order to investigate its possible recovery. This paper presents a preliminary investigation of the sludge resulting from different types of silicatic stones with the aim of their valorization. The investigation was conducted on sludge from cutting with diamond wire, diamond saw blades, and mixed sludge resulting from the filter press. The following tests have been performed to characterize the sludge properties: chemical analysis on the solid fraction of sludge, particle size distribution, evaluation of the metals content through image analysis for each particle size, and leaching tests. To assess the possible recovery of the sludge, wet magnetic separation tests with a high gradient magnetic separator were performed in order to obtain two types of secondary materials, namely the mineral fraction and metals fraction. The separation efficiency has been evaluated through DRX and SEM analysis on the two fractions. The results obtained for the different particle size classes have been compared. The magnetic separation of the size class <0.038 mm has a low separation efficiency because of the phenomenon of grain capture by metallic granules: for this reason the metallic fraction of this class must be further processed if it is to be considered as a secondary raw material. On the other hand, the magnetic separation of the other granulometric classes is characterized by good separation efficiency. A good efficiency of the process is a key factor in order to optimize the recovery process and to increase the economic advantages. The study performed is useful for evaluating the possible reuse of both the metal and the mineral parts, through the implementation of a proactive waste management strategy in order to avoid a subsequent environmental degradation. Highlights: Implementation of a proactive waste management strategy in order to avoid a subsequent environmental degradation. Reduction of waste generated. Decreased use of "Critical Raw Materials". No landfill disposal of sludge and the reduction of soil contamination potential. Prevention of hazardous waste transport and cost reduction.